The effect of FGD gypsum addition in the mixture of shotcrete used bottom ash as fine aggregate - Pisut Rodvinij (2019)
© Int. J. of GEOMATE. Shotcrete used for temporary or permanent protection of slope in Mae Moh mine that may deteriorate when exposed to the weather change. In order to improve the efficiency and reduced cost of shotcrete, by-product materials from Mae Moh power plant area good alternative to use in the mixture. This study investigated the influence of flue gas desulphurization (FGD) gypsum on the properties of shotcrete used bottom ash as fine aggregate. The mixture of shotcrete was a combination of Portland cement type 1 and bottom ash in a ratio of 1:3. The addition of FGD gypsum in the mixture was 4%, 8% and 12% by weight of cement. Water to cement ratio was 0.6. The results demonstrated the slump flow of shotcrete decreased withFGD gypsum increment. However, the setting time of shotcrete was longer with FGD gypsum increment. The addition of FGD gypsum in the mixture at 12% can be reduced the shrinkage approximately 100 microstrains. The addition of FGD gypsum at 4% in the mixture can be developed the compressive strength approximately 8-20% of shotcrete without FGD gypsum. Moreover, the compressive strength and durability of shotcrete mixed with FGD gypsum at 4% could be able to give the highest strength. Nevertheless, the compressive strength and durability of shotcrete tend to decrease with FGD gypsum increment when the mixture containing FGD gypsum exceeds 4%. In conclusion, the addition of FGD gypsum at 4% in the mixture was the most efficient to develop the properties of shotcrete.